Human Health Risks from Toxic Microalgae: A Critical Narrative Review of Exposure Pathways, Toxin Syndromes and Risk Management - Carlos Prosperi (Annual Research & Review in Biology, 2026)
Harmful algal blooms and toxin-producing micro-organisms create a heterogeneous set of human health hazards that cannot be reduced to a single exposure pathway or clinical syndrome. Marine dinoflagellates and diatoms generate phycotoxins that accumulate in shellfish and finfish or become aerosolised at the sea surface, while toxin-producing freshwater cyanobacteria contaminate drinking and recreational waters and can also enter food webs. This critical narrative review evaluates the strength of evidence linking these hazards to human illness, with emphasis on exposure route, toxicological mechanism, acute syndromes, low-dose and chronic uncertainty, surveillance limitations and public-health control. Literature published from 1985 to 23 June 2026 was considered, with earlier foundational evidence retained where necessary. The strongest human evidence concerns acute paralytic, amnesic, ciguatera, diarrhoeic and azaspiracid shellfish poisoning, brevetoxin-associated respiratory effects, and severe microcystin toxicity following exceptional high-dose exposure. By contrast, evidence for chronic neurological, hepatic or carcinogenic effects from environmentally relevant low-dose exposure is much less secure because exposure reconstruction is imprecise, validated human biomarkers are scarce, case definitions vary, and many studies are ecological, cross-sectional or geographically concentrated. Repeated low-level domoic acid exposure and persistent ciguatera symptoms warrant continued investigation, whereas a causal role of β-N-methylamino-L-alanine in human neurodegenerative disease remains unestablished. Climate warming, eutrophication, hydrological extremes and global seafood trade may alter exposure opportunities, but apparent temporal increases in harmful blooms are partly influenced by intensified monitoring and reporting. Effective prevention therefore depends on toxin-specific monitoring, food and water controls, integrated environmental and clinical surveillance, and risk communication that acknowledges uncertainty. Future progress requires prospective exposure cohorts, harmonised analytical methods, validated biomarkers, clinically meaningful dose–response data and better linkage between environmental measurements and individual health outcomes.